Pinkalicious & Peterrific. Playtime with Pinkalicious! [videorecording (DVD)] (PBS Distribution, 2020)
It's time for fun and games with Pinkalicious! Join Pinkalicious and her brother Peter as they put their gnome thinking caps on to help Norman the Gnome plan the perfect playdate.